2019
DOI: 10.4103/jpbs.jpbs_295_18
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of Curcuma longa L. extract on periodontal pathogens

Abstract: Aim: The aim of this study was to evaluate the antimicrobial activity of Curcuma longa L. extract (CLE) on periodontal pathogens. Materials and Methods: Sixty patients were divided into three groups: Group I ( n = 20) patients treated with scaling and root planning (SRP) only, Group II ( n = 20) patients treated with SRP followed by subgingival irrigation with 1% CLE solution, and Group III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…While the use of systemic medicines against periodontal disease has been shown in several published research with various side effects. 29 Curcumin has been known worldwide for its many health benefits 30 and clinical use of Curcumin as a suitable adjunct in the treatment of periodontitis has been reported by many researchers 31 , 32 , 33 and several others. Therefore, the aim of the current study was to assess the impact of local application of curcumin gels in EPD in rat, depending on its different biological and medicinal properties 34 and to clarify the processes by which this natural plant product acts and compared it with chlorhexidine, the well-known antimicrobial drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the use of systemic medicines against periodontal disease has been shown in several published research with various side effects. 29 Curcumin has been known worldwide for its many health benefits 30 and clinical use of Curcumin as a suitable adjunct in the treatment of periodontitis has been reported by many researchers 31 , 32 , 33 and several others. Therefore, the aim of the current study was to assess the impact of local application of curcumin gels in EPD in rat, depending on its different biological and medicinal properties 34 and to clarify the processes by which this natural plant product acts and compared it with chlorhexidine, the well-known antimicrobial drug.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in conjunction with the curcumin characteristics against periodontitis and probing-depth reduction that several trials have outlined. 32 , 33 , 51 Curcumin may, therefore, be used for oral care and, in particular, for periodontitis due to its antimicrobial activity against periodontal bacteria. 39 It has a potent anti-inflammatory and antioxidant activity, 52 and also because of a it has lesser adverse effect than chlorhexidine drug.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the susceptibility of S. aureus might be due to the variances in the cell wall structure, physiology and metabolism (4). Jalaluddin et al (19) found that C. longa extract was effective on some periodontal pathogens; Porphyromonas gingivalis, Prevotella intermedia and Aggregatibacter actinomycetemcomitans. This indicates that there is at least one substance in C. longa that has antimicrobial effects on many bacterial species.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…This may be attributed to the low dosage of curcumin and the use of curcumin in the form of mouthwashes. Therefore, it is suggested that a higher dosage of curcumin be used to achieve better results (Chainani‐Wu, 2003; Gottumukkala, Sudarshan, & Mantena, 2014; Jalaluddin et al, 2019; Muglikar et al, 2013). In the current study water solubility, absorption in the gastrointestinal tract, and prolonged plasma half‐life were improved by the formulation of curcumin as nano‐curcumin capsule form.…”
Section: Discussionmentioning
confidence: 99%